The Theory of Effectiveness of the State: Institutional Aspect - Kolesnichenko Irina M. (Problemi Ekonomiki, 2016)
The article is devoted to one of the most urgent problems of modern economic theory and practice — effectiveness of the state. The aim of the paper is a comprehensive analysis of institutional aspects of the formation of a new economic theory of effectiveness of the state. To achieve this aim, the author first summarizes the evolution and theoretical and methodological characteristics of the economic theories of the state paying a special attention to the essence of the concept of “state” and focusing on “effectiveness of the state” as a major category of the new economic theory. Then he proceeds to institutional aspects of effectiveness of the state considering it as a specific organization and system of institutions of power and control; defines components of effectiveness of the state generalizing the existing methodological approaches and most importantly — the modern criteria for assessing the effectiveness of the state.